2013
DOI: 10.1007/s40265-013-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Mipomersen Sodium: First Global Approval

Abstract: Mipomersen sodium (Kynamro™) (henceforth mipomersen) is a second-generation antisense oligonucleotide inhibitor of apolipoprotein B-100, which is the main structural component of atherogenic lipid particles. Mipomersen is administered via subcutaneous injection and is indicated as adjunctive treatment for homozygous familial hypercholesterolaemia (HoFH). The drug was developed by Isis Pharmaceuticals, which now collaborates with Genzyme Corporation for on-going development and product marketing. Multinational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…This is due to the convergence of several developments including improved chemistries, better understanding of the basic biology of oligonucleotides, more sophisticated delivery systems and most importantly, increasing success in the clinic. The 2013 approval of the first major antisense drug, Kynamro ® (2), an inhibitor of apolipoprotein B expression, was accompanied by promising clinical trials involving siRNA (3) and splice switching oligonucleotides (SSOs) (4). More recently, a number of clinical trials utilizing various types of oligonucleotides have reported impressive results.…”
Section: An Overview Of Oligonucleotide Therapeuticsmentioning
confidence: 99%
“…This is due to the convergence of several developments including improved chemistries, better understanding of the basic biology of oligonucleotides, more sophisticated delivery systems and most importantly, increasing success in the clinic. The 2013 approval of the first major antisense drug, Kynamro ® (2), an inhibitor of apolipoprotein B expression, was accompanied by promising clinical trials involving siRNA (3) and splice switching oligonucleotides (SSOs) (4). More recently, a number of clinical trials utilizing various types of oligonucleotides have reported impressive results.…”
Section: An Overview Of Oligonucleotide Therapeuticsmentioning
confidence: 99%
“…In 2013, the FDA approved the second RNA-based drug, mipomersen, which is a 2′-O-methoxyethyl phosphorothioate antisense oligonucleotide targeting apolipoprotein B expressed in the liver [74]. By reducing the amount of this protein that is secreted from the liver into the blood stream, mipomersen successfully decreases low-density lipoprotein cholesterol levels in patients with homozygous familial hypercholesterolemia [75].…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] ISIS-TTR RX is a second-generation chimeric antisense inhibitor of TTR. It binds selectively and with high affinity to the nontranslated portion of the human TTR mRNA and results in its degradation, preventing production of both wt and variant TTR protein.…”
Section: Tafamadismentioning
confidence: 99%